2017
DOI: 10.24070/bjvp.1983-0246.v10i1p2-9
|View full text |Cite
|
Sign up to set email alerts
|

Canine tarsal gland epitheliomas and adenomas: a retrospective study of 290 cases in Brazil

Abstract: Werner, et al.; Canine tarsal gland epitheliomas and adenomas: a retrospective study of 290 cases in Brazil. Braz J Vet Pathol, 2017, 10(1), 2 -9. DOI: 10.24070/bjvp.1983-0246.v10i1p2-9 Brazilian Abstract A total of 290 cases of tarsal gland adenomas and epitheliomas from canine patients were analyzed to determine the frequency and to better characterize their histopathological features. Tissue samples were examined in two veterinary pathology laboratories in Curitiba, Brazil, which receive samples from all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…The most commonly affected structure in our study was the Meibomian gland, agreeing with the literature (Dubielzig, 2017). Werner et al (2017) reported 9.4 years as the average age for Meibomian neoplasms, which is consistent with our findings (9.9 years). Silva et al .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The most commonly affected structure in our study was the Meibomian gland, agreeing with the literature (Dubielzig, 2017). Werner et al (2017) reported 9.4 years as the average age for Meibomian neoplasms, which is consistent with our findings (9.9 years). Silva et al .…”
Section: Discussionsupporting
confidence: 93%
“…(2013) analyzed a considerable number of ocular neoplasms (n = 173) finding numerous cases in dogs over 10 (43.2%) and 6-10 years (40.6%), and few cases in those under 5 years of age (9.9%). Several studies have evaluated ocular neoplasms, observing an age predilection, mainly in dogs between 8 and 11 years of age (Abarca et al ., 2002;Heath et al ., Eye neoplasms in dogs 2003;Laus et al ., 2008;Conceição et al ., 2010;Fernandez, 2013;Werner et al ., 2017). These reports are in agreement with our findings, where the age group with the highest incidence (8-11 years of age) presented significant difference when compared to the other age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation